THE RELATIONSHIP OF ACADEMIC PROCRASTINATION WITH STRESS, ANXIETY, AND DEPRESSION DURING THE COVID-19 PANDEMIC IN STUDENTS OF THE MEDICAL STUDY PROGRAM, FACULTY OF MEDICINE, UNDIP - Melania Tiara Cahyaratri; Fanti Saktini; Hang Gunawan Asikin; Tanjung Ayu Sumekar (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2022)
Background: Academic procrastination is defined as a learner's tendency to delay learning-related activities, which in many cases eventually causes anxiety and stress. Studying at home tends to cause a feeling of having a lot of free time, eventually postponing work. Students who often procrastinate tend to experience anxiety and depression more often than students who do not procrastinate.Aim: To prove the relationship between academic procrastination and stress, anxiety, and depression due to the COVID-19 pandemic.Method: This research was a cross-sectional study with 184 respondents. The research was conducted in November 2021. The respondents were UNDIP medical students batch 2020. The questionnaires used were the Procrastination Academic Scale for Student (PASS) and Depression, Anxiety, Stress Scale-21 (DASS-21). Data were taken from the questionnaire after the respondents agreed to the informed consent and were analyzed using the Spearman correlation test.Results: As many as 70,1% of respondents were female. Almost 50% of students have a high level of procrastination. A total of 21.7% of students experienced severe to very severe stress, 55.4% experienced severe to very severe anxiety, and as many as 50.4% experienced severe to very severe depression. The level of academic procrastination was positively correlated with stress levels (r=0.468, p<0.001), anxiety levels (r=0.468, p<0.001), and depression levels (r=0.401, p<0.001).Conclusion: Academic procrastination with stress, anxiety, and depression during the COVID-19 pandemic has a significant relationship with a moderate positive correlation.Keywords: Procrastination ; Stress ; Anxiety ; Depression ; COVID-19 Pandemic.